2007
DOI: 10.1177/000348940711600707
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Cochlear Nerve Hypoplasia with Various Internal Auditory Meatus Deformities in Children

Abstract: The risk of co-involvement of the inner ear and superior vestibular nerve functions is higher in the presence of a narrower bony IAM. Cochlear nerve hypoplasia is proposed as one of the most important causes of juvenile unilateral deafness because of its unexpectedly high incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…It is suggested that vestibular dysfunction involves both the superior and inferior vestibular nerve in the majority of CND cases with vestibular dysfunction. Ito et al reported pathological caloric responses in 5 of 10 patients with unilateral CND, although cVEMP showed normal responses in all 9 patients, suggesting that the superior vestibular nerve is more frequently affected than the inferior vestibular nerve [8]. Unlike previous reports, the present study clearly showed that both the superior and inferior vestibular nerves may frequently be impaired.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…It is suggested that vestibular dysfunction involves both the superior and inferior vestibular nerve in the majority of CND cases with vestibular dysfunction. Ito et al reported pathological caloric responses in 5 of 10 patients with unilateral CND, although cVEMP showed normal responses in all 9 patients, suggesting that the superior vestibular nerve is more frequently affected than the inferior vestibular nerve [8]. Unlike previous reports, the present study clearly showed that both the superior and inferior vestibular nerves may frequently be impaired.…”
Section: Discussioncontrasting
confidence: 68%
“…In the cases with VND, the IAC diameter was significantly smaller compared with the cases without VND. A previous report has shown that when the diameter of the IAC is smaller, deterioration of vestibular function tends to occur [8]. When the IAC is smaller, it is often difficult to distinguish and ascertain the presence of the nerve in the IAC even with high-resolution MRI, as in Case No.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is in large part due to the fact that high-resolution MRI has only recently become widely available. However, even with limited existing data, we and others have been finding that it is far from rare [22,24]. The present study further suggests that CND is a remarkably common cause of unilateral hearing loss, particularly when accompanied by intact outer hair cell function.…”
Section: Cochlear Nerve Deficiencysupporting
confidence: 56%
“…Unilateral hearing loss is more common than bilateral [20], and it was previously reported that more than one out of ten children initially diagnosed with unilateral hearing loss will progress to bilateral hearing loss [21][22][23]. Cochlear nerve deficiency is the most common type of malformation observed in the setting of congenital unilateral hearing loss [24][25][26]. Although there are reports of familial unilateral hearing loss [27][28][29][30], genetic mutations associated specifically with unilateral hearing loss have yet not been identified with certainty [31].…”
Section: Discussionmentioning
confidence: 99%